Trophectoderm formation: regulation of morphogenesis and gene expressions by RHO, ROCK, cell polarity, and HIPPO signaling. Issue 4 (22nd August 2022) - Alarcon, Vernadeth B; Marikawa, Yusuke
Abstract : In brief: Trophectoderm is the first tissue to differentiate in the early mammalian embryo and is essential for hatching, implantation, and placentation. This review article discusses the roles of Ras homolog family members (RHO) and RHO-associated coiled-coil containing protein kinases (ROCK) in the molecular and cellular regulation of trophectoderm formation. Abstract: The trophectoderm (TE) is the first tissue to differentiate during the preimplantation development of placental mammals. It constitutes the outer epithelial layer of the blastocyst and is responsible for hatching, uterine attachment, and placentation. Thus, its formation is the key initial step that enables the viviparity of mammals. Here, we first describe the general features of TE formation at the morphological and molecular levels. Prospective TE cells form an epithelial layer enclosing an expanding fluid-filled cavity by establishing the apical-basal cell polarity, intercellular junctions, microlumen, and osmotic gradient. A unique set of genes is expressed in TE that encode the transcription factors essential for the development of trophoblasts of the placenta upon implantation. TE-specific gene expressions are driven by the inhibition of HIPPO signaling, which is dependent on the prior establishment of the apical-basal polarity. We then discuss the specific roles of RHO and ROCK as essential regulators of TE formation. RHO and ROCK modulate the actomyosin cytoskeleton, apical-basal polarity, intercellular junctions, and HIPPO signaling, thereby orchestrating the epithelialization and gene expressions in TE. Knowledge of the molecular mechanisms underlying TE formation is crucial for assisted reproductive technologies in human and farm animals, as it provides foundation to help improve procedures for embryo handling and selection to achieve better reproductive outcomes.